Rapid determination of furanocoumarins in creams and pomades using SPE and GC - Cardoso, CAL; Vilegas, Wagner [UNESP]; Honda, N. K. (Elsevier B.V., 2000)
A solid-phase extraction and chromatography-flame ionization detection (GC-FID) method has been developed for the routine analysis of psoralen, bergapten, isopimpinellin and pimpinellin in creams and pomades employed in Brazil for the treatment of vitiligo. The calibration curve for psoralen was linear in the range 10-100 mu g ml(-1), for bergapten 5-90 mu g ml(-1), for pimpinellin 10-90 mu g ml(-1) and for isopimpinellin 5-100 mu g ml(-1). The best recoveries of the furanocoumarins in the creams analysed were 94-97%, whereas in the pomades, recoveries were 94-96%. The R.S.D. of the quantitative analysis of the furanocoumarins in the products analyses were within 5%. (C) 2000 Elsevier B.V. B.V. All rights reserved.
Keywords: gas chromatography; furanocoumarins; psoralens; vitiligo; creams; pomades